Prediabetes Is Associated with HNF-4α P2 Promoter Polymorphism rs1884613: A Case-Control Study in Han Chinese Population and an Updated Meta-Analysis. (15th October 2014) - Wang, Changyi; Chen, Sihan; Zhang, Tao; Chen, Zhongwei; Liu, Shengyuan; Peng, Xiaolin; Ma, Jianping; Zhong, Xiaohong; Yan, Yanqiong; Tang, Linlin; Mai, Yifeng; Han, Liyuan; et al.
Abstract : Background . Controversy remains for the association between hepatocyte nuclear factor 4α ( HNF-4α ) P2 promoter polymorphism rs1884613 and type 2 diabetes (T2D). There was no association test of this polymorphism with prediabetes and T2D in the Chinese population. Moreover, an updated meta-analysis in various ethnic groups is needed to establish the contribution of rs1884613 to T2D risk. Methods . Using the Sequenom MassARRAY platform approach, we genotyped rs1884613 of HNF-4α in the P2 promoter region among 490 T2D patients, 471 individuals with prediabetes, and 575 healthy controls. All the individuals were recruited from 16 community health service centers in Nanshan district in Shenzhen province. Using STATA 11.0 software, meta-analysis was performed to summarize the overall contribution of rs1884613 to T2D risk. Results . Polymorphism rs1884613 was associated with genetic susceptibility to prediabetes in the whole samples (OR = 1.40, 95% CI = 1.16–1.68, P = 0.0001 ) and the female subgrouped samples (OR = 1.48, 95% CI = 1.14–1.92, P = 0.003 ) after adjusting for age and body mass index (BMI). In contrast, there was no association of rs1884613 with T2D in the whole samples and male in our case-control study and meta-analysis. Conclusions . Our results suggest that rs1884613 contributes to susceptibility to prediabetes, whereas this polymorphism may not play an important role in the development of T2D.